2021
DOI: 10.1080/17483107.2021.1890843
|View full text |Cite
|
Sign up to set email alerts
|

A high prevalence of manual wheelchair rear-wheel misalignment could be leading to increased risk of repetitive strain injuries

Abstract: Purpose: To determine the prevalence and severity of manual wheelchair rear wheel misalignment in community-dwelling manual wheelchair users and estimate the associated increases in rolling resistance (RR) and risk of repetitive strain injuries (RSIs). Materials and Methods: Data were collected in an outpatient rehabilitation clinic, a university research laboratory, and at adaptive sporting events in the United States. Two hundred active, self-propelling manual wheelchair users were recruited. Angular misalig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are many possible reasons, including concerns about stranding if a pneumatic tire went flat, user history that carries over to new wheelchair orders, default options on equipment order forms, difficulty with air pressure maintenance, lack of awareness of importance by clinicians or suppliers, or lack of time during clinic visit to discuss options to minimize RR. Ott et al 34 also found that pneumatic tires were significantly underinflated, with average inflation of 40%, but that RR for underinflated tires was still significantly lower than for airless insert tires. Component-level test results would help clinicians, suppliers and MWU’s to quantify equipment options relative to clinical practice guidelines and help inform choices for minimizing RR, which may result in optimized equipment selection and/or development of lower RR solid tires and casters.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are many possible reasons, including concerns about stranding if a pneumatic tire went flat, user history that carries over to new wheelchair orders, default options on equipment order forms, difficulty with air pressure maintenance, lack of awareness of importance by clinicians or suppliers, or lack of time during clinic visit to discuss options to minimize RR. Ott et al 34 also found that pneumatic tires were significantly underinflated, with average inflation of 40%, but that RR for underinflated tires was still significantly lower than for airless insert tires. Component-level test results would help clinicians, suppliers and MWU’s to quantify equipment options relative to clinical practice guidelines and help inform choices for minimizing RR, which may result in optimized equipment selection and/or development of lower RR solid tires and casters.…”
Section: Discussionmentioning
confidence: 94%
“…Ott et al 34 surveyed two hundred MWU’s and found that about half of manual wheelchairs utilized solid or airless insert tires, despite higher RR. There are many possible reasons, including concerns about stranding if a pneumatic tire went flat, user history that carries over to new wheelchair orders, default options on equipment order forms, difficulty with air pressure maintenance, lack of awareness of importance by clinicians or suppliers, or lack of time during clinic visit to discuss options to minimize RR.…”
Section: Discussionmentioning
confidence: 99%